THE EXPANDING PROTECTION OF MEMBERS OF A PARTY'S OWN ARMED FORCES UNDER INTERNATIONAL CRIMINAL LAW - Yvonne McDermott Rees (International and Comparative Law Quarterly, 2019)
Does international law govern how states and armed groups treat their own forces? Do serious violations of the laws of war and human rights law that would otherwise constitute war crimes or crimes against humanity fall squarely outside the scope of international criminal law when committed against fellow members of the same armed forces? Orthodoxy considered that such forces were protected only under relevant domestic criminal law and/or human rights law. However, landmark decisions issued by the International Criminal Court (ICC) and the Extraordinary Chambers in the Courts of Cambodia (ECCC) suggest that crimes committed against members of the same armed forces are not automatically excluded from the scope of international criminal law. This article argues that, while there are some anomalies and gaps in the reasoning of both courts, there is a common overarching approach under which crimes by a member of an armed group against a person from the same forces can be prosecuted under international law. Starting from an assessment of the specific situation of the victim, this article conducts an in-depth analysis of the concepts of ‘hors de combat’ and ‘allegiance’ for war crimes and that of the ‘lawful target’ for crimes against humanity, providing an interpretative framework for the future prosecution of such crimes.